Separation by enclathration - Corin, Kirsten Claire (Department of Chemistry, 2024)
In this thesis the inclusion properties of the host compounds, 9,9'-(1,4-Phenylene)bis(fluoren-9-ol) (WEB9) and 1, 1,2,2-tetraphenyl-1,2-ethane diol (TPED) were investigated. These host compounds are large, bulky and rigid, they contain functionality that allows them to selectively interact with other molecules, such as the chosen guests in this work. Such host···guest interactions are the central topic under study. The host molecules form inclusion complexes with small organic guest molecules. The host TPED complexes with the guests; 2-picoline, 3-picoline, 4-picoline, toluene, chlorobenzene, bromobenzene, iodobenzene, dioxane, morpholine, piperazine and pyridine. It was used in the two-component separation of dioxane and morpholine, in the two- and three-component separation of the isomers of picoline as well as in the two-, three- and four-component separation of toluene and the halo-substituted benzenes. Along with the isomers of picoline, the effects of adding a neutral solvent as well as changing crystallization temperature were investigated. The host WEB9 complexes with the guests; aniline, benzylamine, 2-phenylethylamine, (S)-methylbenzylamine, (R,S)-methylbenzylamine, pyridine, 2-picoline, 3-picoline, 4-picoline, dioxane, morpholine and p-xylene. It was used in the two-component separation of aniline and benzylamine, in which the effect of a pH change was investigated. The structures of the complexes were elucidated using single crystal X-ray diffraction. Thermal analysis was performed in order to determine the thermal character of the complex, including techniques such as thermogravimetry, differential thermal analysis, hot stage microscopy and differential scanning calorimetry. The kinetics of enclathration of certain guests in the vapour phase were investigated using an automated magnetic suspension balance. The interaction potential of a series of guests was determined by packed column gas chromatography, in which a column was partially packed with either of the two host compounds and guests were passed through it. Competition experiments were performed to determine the selectivity of a host for a series of related guests. These experiments were initially conducted between pairs of guests and then later expanded to three- and four-component systems. The effect of changing the conditions of the competition experiment were investigated by; changing the pH, adding a neutral solvent as well as changing the temperature of crystallization.